Layout Lean model of production management based on change management to improve efficiency in the production of packaging in auto parts sector SMEs - Mancilla-Escobar, J. (2020)
This investigation proposes a lean model of production management for a small and micro enterprise (SME) dealing in packaging production in the auto parts sector, with the purpose of increasing efficiency in its production line. To this end, this model integrates study method tools and SMED, seeking to reduce waiting times and unnecessary operations, which have been identified as causing the problem on the basis of an initial diagnosis of the situation. Furthermore, to support and guarantee success in implementing these tools, John Kotter's Change Model is used. After two months of implementation, the results showed a 50% reduction in setup operation time and a 32% decrease in filing operation time, which are bottlenecks in the production process. Thus, with the new indicators, the line efficiency increased by 7% from the initial situation, thus showing improvement.